2005
DOI: 10.1182/blood.v106.11.260.260
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle-Associated Tissue Factor Activity: A Link between Cancer and Thrombosis?.

Abstract: Background: Cancer, in particular mucinous adenocarcinomas, is associated with an increased risk of venous thromboembolism (VTE). Tissue factor (TF), a transmembrane-receptor protein and initiator of coagulation, plays a central role in the paradigm that clotting and tumor growth form a vicious circle, in which hypercoagulability facilitates the aggressive biology of cancer and vice versa. Expression of TF is associated with poor differentiation of tumors and poor prognosis. We initiated a study in cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
199
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(210 citation statements)
references
References 0 publications
9
199
1
1
Order By: Relevance
“…), and recently the levels of circulating EVs associated with tissue factor (TF), an important activator of extrinsic coagulation pathways, was linked to the increased risk of venous thromboembolism in cancer patients (Tesselaar et al . ). Vascular thrombosis due to atherosclerotic plaque rupture is the main cause of vascular occlusion events including myocardial infarction, unstable angina, stroke and sudden cardiac death.…”
Section: Exosomes Released From Vascular Smooth Cells Mediate Calcifimentioning
confidence: 97%
“…), and recently the levels of circulating EVs associated with tissue factor (TF), an important activator of extrinsic coagulation pathways, was linked to the increased risk of venous thromboembolism in cancer patients (Tesselaar et al . ). Vascular thrombosis due to atherosclerotic plaque rupture is the main cause of vascular occlusion events including myocardial infarction, unstable angina, stroke and sudden cardiac death.…”
Section: Exosomes Released From Vascular Smooth Cells Mediate Calcifimentioning
confidence: 97%
“…The release of MP occurs upon cell activation and during apoptosis [2]. Elevated concentrations of MP have been associated with clinical conditions, including vascular diseases, diabetes, severe trauma and several types of cancers [3–9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, levels of TF are associated with the aggressiveness of cancer and thus poor patient prognosis (Kato et al, 2005). Reports have indicated that cancer patients present high rates of thrombosis due to elevated levels of TF microparticles, presumably originating from cancer cells that circulate in their plasma (Tesselaar et al, 2007; Kasthuri et al, 2009; Krikun et al, 2010). The first interesting observation to stem from this study was the demonstration that progesterone increases the levels of TF in heavy membrane fractions, whereas the coagulant activity of TF was by and large restricted to the cholesterol‐rich lipid rafts where TF protein was extremely low.…”
Section: Discussionmentioning
confidence: 99%